2022
DOI: 10.1155/2022/9708829
|View full text |Cite|
|
Sign up to set email alerts
|

Abnormal GRHL2 Methylation Confers Malignant Progression to Acute Leukemia

Abstract: Purpose. Abnormal methylation of Grainyhead-like 2 (GRHL2) is associated with a substantial role in the malignant phenotype of tumor patients. Our present research is aimed at studying the abnormal expression of GRHL2 and the association of methylation in patients with acute leukemia and its relationship with prognosis. Materials and Methods. We used quantitative real-time polymerase chain reaction (qRT-PCR) for detecting the aberrant expression level of GRHL2 in 60 patients with acute leukemia and 60 normal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 50 publications
(55 reference statements)
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%